2018
DOI: 10.1042/bsr20180114
|View full text |Cite
|
Sign up to set email alerts
|

The association of polymorphisms in nucleotide excision repair genes with ovarian cancer susceptibility

Abstract: Nucleotide excision repair (NER), the core mechanism of DNA repair pathway, was commonly used to maintain genomic stability and prevent tumorigenesis. Previous investigations have demonstrated that single nucleotide polymorphisms (SNPs) of NER pathway genes were associated with various types of cancer. However, there was no research elucidating the genetic association of entire NER pathway with ovarian cancer susceptibility. Therefore, we conducted genotyping for 17 SNPs of six NER core genes (XPA, XPC, XPG, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…This complex also plays a role in the HR pathway, repairing intra-strand crosslink. There is conflicting data regarding the validity of ERCC1 as a predictive biomarker of platinum resistance [47,[49][50][51][52][53][54][55][56][57]. Polymorphisms in other NER components (i.e., XPA, XPB, XPF, XPD) have shown no correlation with platinum resistance [58].…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…This complex also plays a role in the HR pathway, repairing intra-strand crosslink. There is conflicting data regarding the validity of ERCC1 as a predictive biomarker of platinum resistance [47,[49][50][51][52][53][54][55][56][57]. Polymorphisms in other NER components (i.e., XPA, XPB, XPF, XPD) have shown no correlation with platinum resistance [58].…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…About half of the patients are photosensitive because they bear the mutation in XPB/ERCC3, XPD/ERCC2, or general transcription factor IIH subunit 5 (GTF2H5) [153]. Zhao et al analysed 17 SNPs in NER genes XPA, XPC, XPD/ERCC2, XPF/ERCC4, XPG, and ERCC1 in 89 OvC cases and 356 controls, and their results suggested that ERCC1, XPC, and XPD/ERCC2 may be linked to OvC susceptibility [154]. Although this study for the first time explored the association of core genes in NER pathway with OvC, it should be pointed out that the sample size was insufficient to link OvC susceptibility to particular genetic variations and further, authors were not able to measure the mRNA expression of ERCC1, XPC, and XPD/ERCC2 to validate their findings.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…Ishibashi et al reported that in OvC cell lines, tyrosine kinase with immunoglobulin-like and EGF like domains 1 (TIE1) promotes XPC-dependent NER and this leads to decreased susceptibility to cisplatin-induced cell death [158]. Last but not least, a study in 559 EOC patients showed an association of ERCC1 polymorphisms rs11615 and rs3212986 with cisplatin resistance Zhao et al analysed 17 SNPs in NER genes XPA, XPC, XPD/ERCC2, XPF/ERCC4, XPG, and ERCC1 in 89 OvC cases and 356 controls, and their results suggested that ERCC1, XPC, and XPD/ERCC2 may be linked to OvC susceptibility [154]. Although this study for the first time explored the association of core genes in NER pathway with OvC, it should be pointed out that the sample size was insufficient to link OvC susceptibility to particular genetic variations and further, authors were not able to measure the mRNA expression of ERCC1, XPC, and XPD/ERCC2 to validate their findings.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…Together with the Xeroderma pigmentosum F it forms an endonuclease, which also participates in homologous recombination and base excision repair (BER) 16. The ERCC1 protein plays crucial role in NER, so some studies suggested that ERCC1 polymorphisms could attribute to increased risk of several malignant diseases 17,18. The gene for the ERCC1 protein is located on the chromosome 19q13.32 and consists of 10 exons 19.…”
Section: Introductionmentioning
confidence: 99%